1992
DOI: 10.1002/ajmg.1320420113
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of ophthalmologic findings in myotonic dystrophy: Comparison with risks calculated by haplotype analysis of closely linked restriction fragment length polymorphisms

Abstract: To determine diagnostic value of lens opacities in myotonic dystrophy (DM), we examined 98 at-risk members of 9 DM kindreds. Haplotype analysis of restriction fragment length polymorphisms (RFLPs) using ApoC2, CKMM, and pEFD4.2 supported the diagnosis of DM in 33 and excluded the diagnosis in 51 members. The sensitivities of bilateral iridescent lens opacities, posterior cortical lens opacities, orbicularis oculi weakness, low intraocular pressure, ptosis, and ocular myotonia were 46.7, 50.0, 60.6, 59.3, 51.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, subsequent molecular analysis showed that most such subjects in this and other kindreds did not carry the myotonic dystrophy mutation 816 By contrast, Ashizawa et al ,17 analysing lens opacities alone in a series of 98 subjects at risk, found 100% specificity for opacities considered characteristic, when compared with a prediction from closely linked DNA markers. Outside the family context, lens opacities are less specific, Giordano et al 18 finding apparently characteristic lens opacities in 10 of 1400 healthy subjects, none of whom showed the myotonic dystrophy mutation.…”
Section: Discussionmentioning
confidence: 81%
“…However, subsequent molecular analysis showed that most such subjects in this and other kindreds did not carry the myotonic dystrophy mutation 816 By contrast, Ashizawa et al ,17 analysing lens opacities alone in a series of 98 subjects at risk, found 100% specificity for opacities considered characteristic, when compared with a prediction from closely linked DNA markers. Outside the family context, lens opacities are less specific, Giordano et al 18 finding apparently characteristic lens opacities in 10 of 1400 healthy subjects, none of whom showed the myotonic dystrophy mutation.…”
Section: Discussionmentioning
confidence: 81%
“…The formation of cataracts in the eye lens and the myotonia of skeletal muscle are the most penetrant phenotypes in DM patients [Ashizawa et al, 1992b]. Furthermore, DMPK mRNA and protein are expressed in the epithelial and cortical fiber cells of human and bovine lenses [Dunne et al, 1996a].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, bilateral cortical irides cent and posterior cortical lens opacities were found in 1 in every 140 individuals in the Ital ian population with a sevenfold higher fre quency than that reported by Ashizawa et al [7], Actually the 3 patients who underwent cataract surgery in group I could represent a distortion factor in the calculation of the fre quency of cataract in the tested population sample. However, approximately the same None of the individuals with the described lens opacities showed preclinical neurological signs of DM.…”
Section: Discussionmentioning
confidence: 68%
“…Two further analogous cases were re ported by MacMillan et al [10] and Reardon et al [ 11 ]. Contrarily to that seen by Ashizawa et al [7], these studies suggest that not all cases of early cataract typical of DM are corre lated to the presence of the mutation in the DM gene, even in affected families, and that a reassessment of the specificity of the ophthal mic sign in DM is required.…”
Section: Specificity O F Cataract In Myotonic Dystrophymentioning
confidence: 80%
See 1 more Smart Citation